2021
DOI: 10.3390/jcm10163595
|View full text |Cite
|
Sign up to set email alerts
|

Severe Lymphopenia as a Predictor of COVID-19 Mortality in Immunosuppressed Patients

Abstract: Background. Coronavirus disease 2019 (COVID-19) has a high mortality in certain group of patients. We analysed the impact of baseline immunosuppression in COVID-19 mortality and the role of severe lymphopenia in immunocompromised subjects. Methods. We analysed all patients admitted with COVID-19 in a tertiary hospital in Madrid between March 1st and April 30th 2020. Epidemiological and clinical data, including severe lymphopenia (<500 lymphocytes/mm3) during admission, were analysed and compared based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In addition, the Charlson Comorbidity Index (CCI), which is a well-validated composite that predicts clinical outcomes in multiple illnesses, was calculated from the previous data [ 17 ]. Among other medical conditions, it included diabetes, heart failure, dementia, chronic kidney disease, liver disease and cancer, most of which have been associated with severe COVID-19 [ 3 , 4 , 6 ]. However, we excluded connective tissue disease from this index in order to analyze SAD as a separate variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the Charlson Comorbidity Index (CCI), which is a well-validated composite that predicts clinical outcomes in multiple illnesses, was calculated from the previous data [ 17 ]. Among other medical conditions, it included diabetes, heart failure, dementia, chronic kidney disease, liver disease and cancer, most of which have been associated with severe COVID-19 [ 3 , 4 , 6 ]. However, we excluded connective tissue disease from this index in order to analyze SAD as a separate variable.…”
Section: Methodsmentioning
confidence: 99%
“…In parallel, other authors identified better outcomes in the immunocompromised population and proposed a possible protecting role of a weaker immune response [ 5 ]. By contrast, other cohorts have indeed confirmed that baseline immunodeficiencies are associated with worse prognosis [ 6 , 7 ]. Taken together, it seems that the distinct etiologies of impaired immunity and the drugs prescribed for treatment might explain these differences in COVID-19 outcomes [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The literature search revealed an increased mortality rate in immunocompromised patients with COVID-19. Martinez-Urbistando et al showed that illnesses causing immunodeficiency are an independent risk factor for increased mortality 5 . Mehta et al studied mortality rates in COVID-19 patients with active cancer and found a higher overall mortality rate of 28%; 25% in solid cancers and 37% in haematological cancer 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In detail, 14 patients required no oxygen supplementation at first CP administration, 18 had low-flow oxygen requirement, 14 were receiving high-flow oxygen therapy or non-invasive ventilation (HF/NIV), 5 were intubated (IMV) and 4 received extracorporeal membrane oxygenation (ECMO) support. Patients received a median of 3 CPs (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14], with a mean of 7 days (range, 0-59) after symptom onset.…”
mentioning
confidence: 99%